Implementation of accounting record using accurate software at CV. Tresna - Dewi, Ni Komang Urip Krisna; Premananda, Ni Luh Putu Uttari (Journal of Applied Sciences in Accounting, Finance, and Tax, 2024)
Along with the development of this CV, it has experienced very rapid improvements, and this includes financial management. The results of interviews with accounting CV Tresna stated that currently CV still uses manual recording using Microsoft Excel. This starts from recording receipts from customers, payments to suppliers to financial reports. Technology is needed to make it easier to record and prepare accurate financial reports. Therefore, an accounting information system is needed. An Accounting Information System (AIS) is a collection of resources, such as people and tools designed to convert financial and other data into information. In this research, system accounting information applied is Accurate Accounting Software. Accurate is a program accounting and finance designed to meet company needs in terms of accounting and financial records. This type of research uses qualitative research which is descriptive qualitative. The author implemented Accurate in CV Tresna through several series stages. Starting from a preliminary study, conducting analysis with interview, implementation, testing using the black-box method, to results evaluation and improvement. The results show that Accurate system makes it easier to carry out bookkeeping for creating invoices to customers, paying bills to suppliers, automatic COGS calculations, and financial reports on CV X has been successfully carried out as proof of financial statements to the owner of CV Tresna